2020
DOI: 10.1038/s41598-020-63389-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 5 in bulimia nervosa

Abstract: Bulimia nervosa (BN) shares central features with substance-related and addictive disorders. The metabotropic glutamate receptor subtype 5 (mGlu5) plays an important role in addiction. Based on similarities between binge eating and substance-related and addictive disorders, we investigated mGlu5 in vivo in 15 female subjects with BN and 15 matched controls. We measured mGlu5 distribution volume ratio (DVR) with positron emission tomography (PET) using [11 C]ABP688. In BN mGlu5 DVR was higher in the anterior ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…These diet-related physiological oscillations of tonic neuronal activities could become deteriorated in a diseased condition, as altered mGluR5 availability was shown to emerge in diverse neuropsychiatric disorders. 48 52 A murine model of neurodegenerative diseases also exhibited declines of mGluR5 radioligand binding in our recent PET experiments. 52 We therefore postulate that glucose-induced increase and fasting-induced decrease of ( E )-[ 11 C]ABP688 binding can be dysregulated at a prodromal stage of these illnesses, which might offer biological tests to assist the clinical diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…These diet-related physiological oscillations of tonic neuronal activities could become deteriorated in a diseased condition, as altered mGluR5 availability was shown to emerge in diverse neuropsychiatric disorders. 48 52 A murine model of neurodegenerative diseases also exhibited declines of mGluR5 radioligand binding in our recent PET experiments. 52 We therefore postulate that glucose-induced increase and fasting-induced decrease of ( E )-[ 11 C]ABP688 binding can be dysregulated at a prodromal stage of these illnesses, which might offer biological tests to assist the clinical diagnosis.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the role of mGluR5 on eating disorders was assessed by several authors ( Bradbury et al, 2005 ; Bisaga et al, 2008 ; Guardia et al, 2011 ). More recently, interesting work described the part of mGluR5, in vivo , in bulimia nervosa ( Mihov et al, 2020 ). In this study, the authors found higher distribution volume of mGluR5 in areas linked to processing emotional and cognitive information related to self-control, as anterior cingulate cortex and medial orbitofrontal cortex in individuals with bulimia ( Mihov et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, interesting work described the part of mGluR5, in vivo , in bulimia nervosa ( Mihov et al, 2020 ). In this study, the authors found higher distribution volume of mGluR5 in areas linked to processing emotional and cognitive information related to self-control, as anterior cingulate cortex and medial orbitofrontal cortex in individuals with bulimia ( Mihov et al, 2020 ). Overall, our data confirm the role of mGluR5 on eating disorders and paved the way for the development of therapeutic strategies focused in the glutamatergic transmission for the treatment of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…This underlying neuroendocrinological dysregulation is not only associated with core facets of ASC etiology, but also has direct functional implications for stress-related psychopathology. A disruption of glutamatergic and GABAergic signaling contributes to the etiology of anxiety disorders (313)(314)(315)(316), PTSD (317), eating disorders (318)(319)(320), OCD (321) and substance use disorders (SUDs) (322,323). The serotonergic, dopaminergic and noradrenergic systems are implicated in MDD, anxiety and SUDs (324)(325)(326) while serotonin is also associated with mood disorders, stress, aggression and anti-social conduct (327)(328)(329), and dopamine is thought to play a role in eating disorders (330,331), executive dysfunction and behavioral inhibition (332,333).…”
Section: From Mal To Neurophysiology Neurochemistry and Behavior: A M...mentioning
confidence: 99%